2003
DOI: 10.1097/00005537-200311000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Expression of intercellular adhesion molecule (ICAM)‐1 in adenoid cystic carcinoma of the head and neck

Abstract: Objectives/Hypothesis: Adenoid cystic carcinoma of the head and neck (ACCHN) is characterized by late recurrence and frequent distant metastasis. Tumor attack by cytotoxic T lymphocytes and macrophages is mediated by the interaction of leukocyte function‐associated antigen (LFA)‐1 on lymphocytes with intercellular adhesion molecule (ICAM)‐1 on the tumor surface. Thus, the reduced expression of ICAM‐1 on tumor cells could contribute to their escape from host immune surveillance. To investigate the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…These observations suggest that the reduced expression of ICAM-1 on tumor cells could prevent efficient association of CTLs to tumor cells, contributing, at least partially, to tumor escape from the host immune surveillance. Indeed, reduced expression of ICAM-1 is associated with poor prognosis in various cancers, such as melanoma (30) and head and neck (31), breast (32), colorectal (33), and ovarian cancers (34). These previous studies also point to the significance of identifying miRs that regulate ICAM-1.…”
Section: Discussionmentioning
confidence: 91%
“…These observations suggest that the reduced expression of ICAM-1 on tumor cells could prevent efficient association of CTLs to tumor cells, contributing, at least partially, to tumor escape from the host immune surveillance. Indeed, reduced expression of ICAM-1 is associated with poor prognosis in various cancers, such as melanoma (30) and head and neck (31), breast (32), colorectal (33), and ovarian cancers (34). These previous studies also point to the significance of identifying miRs that regulate ICAM-1.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have also shown that ICAM‐1 plays an important role in diseases of the head and neck, including otitis media,10 cholesteatoma,11 inner and middle ear inflammation,12, 19, 20 nasal polyposis,21, 22 and carcinoma of the head and neck 13, 23. Systemic administration of anti‐ICAM‐1 antibody in experimental immune‐mediated labyrinthitis showed reduced inflammatory cell infiltration in the scala tympani and the perisaccular tissue of the endolymphatic sac 24.…”
Section: Discussionmentioning
confidence: 99%
“…Also the reduced expression of intercellular adhesion molecule-1 (ICAM-1) may promote immune evasion and metastasis, resulting in poor prognosis in AdCC [69]. Increased expression of the membrane-cytoskeletal linker Ezrin, and its partner CD44V6, has been also associated with a more aggressive behavior [70].…”
Section: (4) Cell Adhesion Proteinsmentioning
confidence: 99%